Cambridge checkpoint lower secondary Science grade 6 - Riley, Peter D (United kingdom : Hodder education, 2021)
The Cambridge Checkpoint Lower Secondary Science for Grade 6 is part of the Cambridge Checkpoint series designed for students in the early years of secondary education (typically ages 11-12). This book is aimed at helping students develop a solid understanding of science through a structured curriculum that covers key topics in biology, chemistry, and physics. The content is aligned with international education standards and prepares students for the Cambridge Checkpoint assessments.
Keywords: Science : Textbook